2015
DOI: 10.1017/jfm.2015.534
|View full text |Cite
|
Sign up to set email alerts
|

Energy-consistent entrainment relations for jets and plumes

Abstract: We discuss energetic restrictions on the entrainment coefficient α for axisymmetric jets and plumes. The resulting entrainment relation includes contributions from the mean flow, turbulence and pressure, fundamentally linking α to the production of turbulence kinetic energy, the plume Richardson number Ri and the profile coefficients associated with the shape of the buoyancy and velocity profiles. This entrainment relation generalises the work by Kaminski et al. (J. Fluid Mech., vol. 526, 2005, pp. 361-376) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(145 citation statements)
references
References 40 publications
11
134
0
Order By: Relevance
“…We plot R/r 0 as a function of z/r 0 in figure 3 and a best fit to the data provides a value of α = 0.11±0.01, where the tolerances indicate the standard deviation within our measurements. This value falls within the range of α = {0.095, 0.15}, the median value being α = 0.12, from the six independent studies for which data are reported within van Reeuwijk & Craske (2015).…”
Section: Validation Of the Piv Datamentioning
confidence: 57%
See 2 more Smart Citations
“…We plot R/r 0 as a function of z/r 0 in figure 3 and a best fit to the data provides a value of α = 0.11±0.01, where the tolerances indicate the standard deviation within our measurements. This value falls within the range of α = {0.095, 0.15}, the median value being α = 0.12, from the six independent studies for which data are reported within van Reeuwijk & Craske (2015).…”
Section: Validation Of the Piv Datamentioning
confidence: 57%
“…As a second method for assessing the entrainment coefficient we consider the findings of van Reeuwijk & Craske (2015) in which they showed, for a time-averaged self-similar pure-plume, that α can be expressed in terms of turbulence production, energy flux and buoyancy effects. This decomposition allows a deeper physical insight of the entrainment coefficient beyond the original hypothesis provided by Morton et al (1956), i.e.…”
Section: Validation Of the Piv Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Atmosphere-Ocean Plume˙Behaviour experimental (Ezzamel et al, 2015) investigations -a good summary of which is presented by van Reeuwijk & Craske (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Here we note a correspondence with turbulent plumes, where a ''pure'' plume will have a constant value for Ri. If the flow has an excess (deficit) of momentum at the source the plume is referred to as forced (lazy) [21,22]; the flow will adjust its own state due to the work done by gravity until it becomes pure. The evolution of Ri for the gravity current in time (Fig.…”
Section: Turbulent Entrainmentmentioning
confidence: 99%